Is 5‐fluorouracil the best candidate for topical chemoprevention of skin cancers in organ transplant recipients?. (1st September 2022) - Samimi, Mahtab
Abstract: Linked Article: Hasan et al. Br J Dermatol 2022; 187:324–337.